2000
DOI: 10.1177/109467050032002
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of Customer Satisfaction after Service Failure and Recovery

Abstract: Relatively little research has addressed the nature and determinants of customer satisfaction following service failure and recovery. Two studies using scenario-based experiments reveal the impact of failure expectations, recovery expectations, recovery performance, and justice on customers’ postrecovery satisfaction. Customer satisfaction was found to be lower after service failure and recovery (even given high-recovery performance) than in the case of error-free service. The research shows that, in general, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
679
6
24

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 794 publications
(753 citation statements)
references
References 56 publications
18
679
6
24
Order By: Relevance
“…Different from a typical service provider whose approach to service recovery is to eliminate service failure and gain customer satisfaction (McCollough, Berry, & Yadav, 2000), airports face a bigger challenge as they do not have much control over these aforementioned parties, apart from asking for collaboration. They are less likely to apply interactional justice, which is a method that offers service recovery through a better manner of service interaction (McColl-Kennedy & Sparks, 2003).…”
Section: Psychological: Airport Anxiety and Airport Fairnessmentioning
confidence: 99%
“…Different from a typical service provider whose approach to service recovery is to eliminate service failure and gain customer satisfaction (McCollough, Berry, & Yadav, 2000), airports face a bigger challenge as they do not have much control over these aforementioned parties, apart from asking for collaboration. They are less likely to apply interactional justice, which is a method that offers service recovery through a better manner of service interaction (McColl-Kennedy & Sparks, 2003).…”
Section: Psychological: Airport Anxiety and Airport Fairnessmentioning
confidence: 99%
“…Previous studies have identified satisfaction as an antecedent of loyalty (Andreassen, 2001;Bloemer & Odekerken-Schröder, 2002;Bruner, Stocklin, & Opwis, 2008;Buttle & Burton, 2002;Cronin, Brady, & Hult, 2000;Mattila, 2004;McCullough, Berry, & Yadav 2000;Parasuraman & Grewal, 2000). Satisfaction, according to Tse & Wilton (1988) and Oliver (1980), is an evaluation made by a person between previously created expectations and the result obtained from the consumption of a product or service; i.e.…”
Section: Satisfaction With Tourism Destinationsmentioning
confidence: 99%
“…A panaszkezelés vizsgálatának a szakirodalomban leggyakrabban hivatkozott elméleti alapja az észlelt igazságosság elmélete (Maxham -Netemeyer, 2002;McCollough et al, 2000;Tax et al, 1998), ami a tár-sadalmi csere és a méltányosság elméletekhez kötődik (Homans, 1961;Walster et al, 1973).…”
Section: Az éSzlelt Igazságosság Elméleteunclassified